2010
DOI: 10.1128/aac.00359-10
|View full text |Cite
|
Sign up to set email alerts
|

ADS-J1 Inhibits HIV-1 Entry by Interacting with gp120 and Does Not Block Fusion-Active gp41 Core Formation

Abstract: We had shown that virus resistance to ADS-J1 was associated with amino acid changes in the envelope glycoprotein, mostly located in the gp120 coding region. Time-of-addition and endocytic virus transfer assays clearly demonstrated that ADS-J1 behaved as a gp120 inhibitor. ADS-J1-resistant virus was cross-resistant to the polyanion dextran sulfate, and recombination of gp120 recovered only the ADS-J1-resistant phenotype. In summary, ADS-J1 blocks an early step of virus entry that appears to be driven by gp120 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…ADS-J1 has been found to inhibit HIV-1 entry into target cells by targeting gp41 and gp120 (23,30,31). Here, we found that ADS-J1 inhibited amyloid fibril formation and antagonized fibril-mediated enhancement of HIV-1 infection.…”
Section: Fig 7 Inhibition Of the Formation Of Semenogelin-derived Amysupporting
confidence: 51%
“…ADS-J1 has been found to inhibit HIV-1 entry into target cells by targeting gp41 and gp120 (23,30,31). Here, we found that ADS-J1 inhibited amyloid fibril formation and antagonized fibril-mediated enhancement of HIV-1 infection.…”
Section: Fig 7 Inhibition Of the Formation Of Semenogelin-derived Amysupporting
confidence: 51%
“…3a). A significantly high virus concentration, roughly 5 g/ml of p24 antigen and Ͼ25-fold higher of the commonly used virus input in drug susceptibility studies in MT-4 cells (20,21), was required to achieve 4 to 5% GFP ϩ cells in cell-free infections. Under these conditions, both AZT and TDF effectively blocked virus replication with similar 50% effective concentrations (EC 50 s) measured either by GFP signal or total viral DNA in target cells (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The time/site of drug action (TOA) assays were done as described [29]. In brief, MT-4 cells were infected with NL4-3 virus at a MOI of 0.5 and incubated for 1 h at 208C in the presence or absence of test compounds (ZDV, AMD3100, T-20, C34, BMS-155 and VIR-353).…”
Section: Time Of Drug Addition and Mode Of Actionmentioning
confidence: 99%